Effectiveness of Video-assisted Distraction Therapy on Childrens Pain Perceptions during Peripheral Venous Cannulation - Bhandari, Menuka; Rai, Munawatee; Gartaula, Puja (Journal of Nepal Health Research Council, 2024)
Background: Relief of pain is a basic need and right of all children; effective pain management requires health professionals to be able to apply several interventions to achieve optimal results. The current study aimed to discover the Effectiveness of Video-assisted Distraction Therapy on Children’s Pain Perceptions during Peripheral Venous Cannulation in Pediatric Wards of Biratnagar, Nepal.Methods: A quasi-experimental study was conducted at Pediatric Wards of different hospitals in Biratnagar. Data collection was done from Feb 27, 2023, to April 28, 2023. Non-probability purposive sampling technique was adopted in selecting the desired sample size. Data was collected through an interview questionnaire and a standard observational checklist, the FLACC pain rating scale. The experimental group received video-assisted distraction therapy as an intervention, while the control group received routine intravenous care from the nurses. Results: There is a significant difference between the pain perception score in the experimental and control group during peripheral venous cannulation (p= <0.001) during and after two minutes of cannulation. Similarly, the level of pain was also different in both groups, 42.5% of children in the experimental group perceived moderate pain, 37.5% perceived mild pain and 20% reported severe pain whereas 92.5% of respondents perceived severe pain and only 7.5% perceived moderate pain during peripheral venous cannulation. Conclusions: Video-assisted Distraction Therapy was very efficient at distracting children from their pain during intravenous cannulation. Keywords: Distraction therapy; pain perceptions; peripheral venous cannulation.